Paleomagnetism and tectonics of Karaginsky Island, Bering Sea (Dataset) ... - D. V. Kovalenko; I. R. Kravchenko-Berezhnoy (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetism and tectonics of Karaginsky Island, Bering Sea ...